2012
DOI: 10.1111/j.1365-2559.2012.04329.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of different techniques for measurement of Ki67 proliferation on reproducibility and prognosis prediction accuracy in breast cancer

Abstract: In node-negative breast cancer without adjuvant systemic treatment, Ki67% by DIA, but not subjective counts, is reproducible and prognostically strong. This casts serious doubt on therapeutic guidelines using subjective counts of Ki67.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
122
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(127 citation statements)
references
References 16 publications
5
122
0
Order By: Relevance
“…Therefore, the standardization of Ki67 assessment is considered more crucial because of its values in clinical practice. However, Ki67 LI measurements by immunohistochemical analysis lack interobserver and interlaboratory reproducibility [9][10][11][12][13]. Currently, there is still no global guideline, with both reproducibility and objective standardization, has been established for Ki67 LI assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the standardization of Ki67 assessment is considered more crucial because of its values in clinical practice. However, Ki67 LI measurements by immunohistochemical analysis lack interobserver and interlaboratory reproducibility [9][10][11][12][13]. Currently, there is still no global guideline, with both reproducibility and objective standardization, has been established for Ki67 LI assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Density of cells in particular tumor area may also influence selection of this area as HS [75]. HS selection is done subjectively and results of these choices (at least in breast cancer) do not necessarily correlated with HS recognized using digital image analysis [73,74]. Automated HS detection may be an alternative [74,76,77,79,80].…”
Section: Hot Spotsmentioning
confidence: 99%
“…Important issue for manual counting is HS recognition, as discussed above. Another critical issue of Ki67 LI is a subjective threshold of stain intensity, which is enough to score a particular nucleus as positive [53,73]. Interestingly, inter-observer variability in scoring breast cancer samples cannot be fully explained by technique of scoring (estimation vs. counting), HS selection, positivity threshold or IHC technique [56].…”
Section: Human Factormentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that counts of Ki67 positive cells by different pathologists were poorly reproducible. Interactive point-weighted counting of Ki67 by morphometric techniques were much more reproducible, but automated digital image analysis (DIA) was the most reproducible and prognostically strongest [9].…”
Section: Introductionmentioning
confidence: 99%